2023
DOI: 10.1007/s00227-023-04284-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of multiple environmental controls on lipid biomarkers in common marine diatoms and dinoflagellates

Zhong Cao,
Rong Bi,
Chuanli Zhang
et al.

Abstract: Ocean-related global changes have altered phytoplankton community structure, especially the diatomdino agellate competition, which further in uences ecosystem structure and functions. The pivotal ecological roles of diatoms and dino agellates are strongly related with their biochemical compositions, while quantitative comparisons of biochemical changes between diatoms and dino agellates under variable environments are still limited. We investigated responses of lipid biomarkers (sterols and fatty acids (FAs)) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 105 publications
0
0
0
Order By: Relevance
“…FIGURE 7 PCA biplot based on the proportions (%) of lipid biomarkers at each station in the surface and deep layer in spring 2017 and summer 2018. negative correlations between EPA and TSW proportions and nonsignificant correlations between DHA and TSW proportions in summer, which can explain significant positive correlations between and TSW proportions. A high level of EPA is a characteristic FA pattern in diatoms (Kelly and Scheibling, 2012;Bi et al, 2014;Cao et al, 2023). The TSW is derived from the South China Sea Warm Current Water (Bian et al, 2013) and characterized by low nutrient concentrations (Chen, 1996;Zhang et al, 2019).…”
Section: Lipid Biomarkers In the Surface Layermentioning
confidence: 99%
See 4 more Smart Citations
“…FIGURE 7 PCA biplot based on the proportions (%) of lipid biomarkers at each station in the surface and deep layer in spring 2017 and summer 2018. negative correlations between EPA and TSW proportions and nonsignificant correlations between DHA and TSW proportions in summer, which can explain significant positive correlations between and TSW proportions. A high level of EPA is a characteristic FA pattern in diatoms (Kelly and Scheibling, 2012;Bi et al, 2014;Cao et al, 2023). The TSW is derived from the South China Sea Warm Current Water (Bian et al, 2013) and characterized by low nutrient concentrations (Chen, 1996;Zhang et al, 2019).…”
Section: Lipid Biomarkers In the Surface Layermentioning
confidence: 99%
“…The TSW is derived from the South China Sea Warm Current Water (Bian et al, 2013) and characterized by low nutrient concentrations (Chen, 1996;Zhang et al, 2019). A recent laboratory study reported significant positive effects of nutrient concentrations on carbon-normalized concentrations of EPA in marine diatom Phaeodactylum tricornutum (Cao et al, 2023). Thus, EPA production in diatoms may reduce in low-nutrient regions where TSW proportions were high, resulting in high DHA/EPA in the surface layer in these regions in summer.…”
Section: Lipid Biomarkers In the Surface Layermentioning
confidence: 99%
See 3 more Smart Citations